Use of radiofrequency in cosmetic dermatology: focus on nonablative treatment of acne scars - Simmons BJ; Griffith RD; Falto-Aizpurua LA; Nouri K (Dove Medical Press, 2014)
Brian J Simmons, Robert D Griffith, Leyre A Falto-Aizpurua, Keyvan Nouri Department of Dermatology and Cutaneous Surgery, University of Miami Miller School of Medicine, University of Miami, Miami, FL, USA Abstract: Acne is a common affliction among many teens and some adults that usually resolves over time. However, the severe sequela of acne scarring can lead to long-term psychological and psychiatric problems. There exists a multitude of modalities to treat acne scars such as more invasive surgical techniques, subcision, chemical peels, ablative lasers, fractional lasers, etc. A more recent technique for the treatment of acne scars is nonablative radiofrequency (RF) that works by passing a current through the dermis at a preset depth to produce small thermal wounds in the dermis which, in turn, stimulates dermal remodeling to produce new collagen and soften scar defects. This review article demonstrates that out of all RF modalities, microneedle bipolar RF and fractional bipolar RF treatments offers the best results for acne scarring. An improvement of 25%–75% can be expected after three to four treatment sessions using one to two passes per session. Treatment results are optimal approximately 3 months after final treatment. Common side effects can include transient pain, erythema, and scabbing. Further studies are needed to determine what RF treatment modalities work best for specific scar subtypes, so that further optimization of RF treatments for acne scars can be determined. Keywords: acne scarring, radiofrequency treatments, nonablative radiofrequency treatments, scars